Vacuolar SNARE Protein Transmembrane Domains Serve as Nonspecific Membrane Anchors with Unequal Roles in Lipid Mixing - Pieren, Michel (J Biol Chem, 2015)
Membrane fusion is induced by SNARE complexes that are anchored in both fusion partners. SNAREs zipper up from the N to C terminus bringing the two membranes into close apposition. Their transmembrane domains (TMDs) might be mere anchoring devices, deforming bilayers by mechanical force. Structural studies suggested that TMDs might also perturb lipid structure by undergoing conformational transitions or by zipping up into the bilayer. Here, we tested this latter hypothesis, which predicts that the activity of SNAREs should depend on the primary sequence of their TMDs. We replaced the TMDs of all vacuolar SNAREs (Nyv1, Vam3, and Vti1) by a lipid anchor, by a TMD from a protein unrelated to the membrane fusion machinery, or by artificial leucine-valine sequences. Individual exchange of the native SNARE TMDs against an unrelated transmembrane anchor or an artificial leucine-valine sequence yielded normal fusion activities. Fusion activity was also preserved upon pairwise exchange of the TMDs against unrelated peptides, which eliminates the possibility for specific TMD-TMD interactions. Thus, a specific primary sequence or zippering beyond the SNARE domains is not a prerequisite for fusion. Lipid-anchored Vti1 was fully active, and lipid-anchored Nyv1 permitted the reaction to proceed up to hemifusion, and lipid-anchored Vam3 interfered already before hemifusion. The unequal contribution of proteinaceous TMDs on Vam3 and Nyv1 suggests that Q- and R-SNAREs might make different contributions to the hemifusion intermediate and the opening of the fusion pore. Furthermore, our data support the view that SNARE TMDs serve as nonspecific membrane anchors in vacuole fusion.